RHINOPLASTY: MODERN SURGICAL APPROACHES, FUNCTIONAL AND AESTHETIC RESULTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Rhinoplasty, one of the most complex and in-demand procedures in plastic and reconstructive surgery, aims to correct the shape of the nose and restore its respiratory function. This article presents a comprehensive review of modern principles, techniques, and clinical aspects of rhinoplasty. The aim of the study is to analyze the evolution of surgical techniques, compare open and closed approaches, evaluate indications for surgery, and systematize data on preoperative planning, postoperative management, and potential complications. Particular attention is paid to the integration of functional and aesthetic goals, a key principle of modern rhinoplasty. Based on a review of the literature and clinical data, it is concluded that the success of rhinoplasty directly depends on a thorough diagnosis, an individualized surgical approach, realistic patient expectations, and strict adherence to rehabilitation protocols. The study results emphasize the role of rhinoplasty not only in improving patients' quality of life by restoring nasal breathing but also in achieving a harmonious aesthetic result that corresponds to the anatomical features and the patient's wishes.